Changes in Candidate Selection and the Sociodemographic Profile of Greek MPs. Evidence From the 2019 General Elections - Kakepaki, Manina (Frontiers in Political Science, 2022)
The July 2019 national elections in Greece marked the return in power of the conservative party of ND, one of the two pillars of the traditional Greek bipartisanism. Turnover in these elections nearly reached 40%; more than two thirds of the current Parliament MPs were first elected during the crisis, since old parliamentarians slowly give away their seats to newcomers. The aim of this paper is twofold: 1) explore candidate selection mechanisms of old and new parties in Greece inquiring what -if any- has changed in these mechanisms after the Great Recession and whether they adopt IPD in a wider extent; and 2) investigate the sociodemographic profile of newcomers vis-à-vis older Parliamentarians in order to check if the outcome of the elections has changed in terms of a more socially diverse profile. Given that the issue of candidate selection (and election) is mostly based on unwritten rules, our findings will rely on written party rules (such as party manifestos), on original sociodemographic data and on personal interviews. We tentatively suggest that not much has changed in the candidate selection mechanisms in Greece. ND made limited use of its open registry of candidates, whilst SYRIZA applied the same rules as in previous elections. We conclude that, the crisis in Greece offered the opportunity structures for the mass renewal of its parliamentary elite and for a somewhat more socially diverse pool of successful candidates, but its effect quickly disappeared since new MPs resemble more independent political entrepreneurs and have less social and political ties.